Mapping the Legal and Philosophical Aspects of Human Rights Education in Religious Studies Towards a Curriculum Restructuring - Dean Collin Langeveldt; Doniwen Pietersen (E-Journal of Religious and Theological Studies)
This article explored the strategic integration of religious education within the framework of human rights literacy that is underpinned by philosophical values in South Africa during a period of significant educational reform. The study examined the integration of religious studies with human rights education, emphasising the importance of human rights literacy in understanding religious diversity and promoting interfaith respect. The analysis examined key pedagogical changes, policy adaptations, and curricular innovations in South Africa’s educational system, forming an integrative pedagogical model. This examination also highlighted diversity on several levels. Internal diversity or differences in how members of the same cultural group or marginalised groups map and understand human rights in religious education. Foregrounded in this work are the educational psychology and sociology theoretical frameworks that intersect to enhance human rights literacy and religious education. The findings showed that the aforementioned educational fields are not just an academic exercise but a social imperative for a more inclusive and respectful place in global education. This conceptual paper focused on the South African experience, offering global insights that may resonate with the South African locality. It is recommended that South Africa’s religious curriculum be inclusive, requiring deep understanding and engaging content, to balance secular and religious education and uphold human rights. The study recommends developing an inclusive curriculum, engaging pedagogical strategies, comprehensive teacher training, and active learning to promote a balanced understanding of religious diversity and human rights. This study impacts scholarship by providing a robust theoretical framework, influencing curriculum development and policy support, and providing global insights for educational reform.